Artifacts of Reddening can Shadow the Postmortem Burns & Manner of Death (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Incidences of homicidal post-mortem burns are increasing day by day. Post-mortem burns are commonly produced to dispose off the body after an obvious crime or to hide the identity of victim or to create confusion regarding the cause of death and its manner. Determination of the cause of death following by autopsy in such cases is always a difficult task for autopsy surgeons and becomes more tedious when burns produced after death belong to the peri-mortem period because changes of reddening produced during peri mortem burning is likely to lead to misinterpretation of postmortem burns and further the manner of death. In a similar case, dead body of a young Muslim male was brought to us for autopsy examination with alleged history of death due to burns, in which the burns present over the body of the victim were showing postmortem characteristics with contradictory artifact of reddening on front parts of the body and typical injuries of throttling over the neck region, which were also under cover of blackening of soot. Effects of artifacts due to reddening and blackening in post-mortem burns noticed in the present case and its medico-legal significances are discussed in detail as the case is rare of its kind.
Keywords: Post-Mortem burns; Artifact; Homicide and Asphyxia